Successful Treatment of Hemophagocytic Lymphohistiocytosis Associated with Lupus Nephritis by Using Mycophenolate Mofetil - Takashi Nawata; Makoto Kubo; Kosaku Shiragami; Yukinori Nakamura; Masafumi Yano (Case Reports in Rheumatology, 2017)
An estimated 0.9% to 2.4% of patients with systemic lupus erythematosus (SLE) also have hemophagocytic lymphohistiocytosis (HLH). HLH associated with autoimmune diseases is often refractory to corticosteroid treatment; thus, additional immunosuppressive drugs, such as cyclosporine, cyclophosphamide, or tacrolimus, are required. Here, we describe the case of a 44-year-old Japanese woman who developed HLH associated with lupus nephritis. Initially, her HLH was refractory to treatment with a corticosteroid, tacrolimus, and mizoribine. However, alternative treatment with a corticosteroid, mycophenolate mofetil, and tacrolimus improved both her HLH and lupus nephritis. This case suggests the possibility of mycophenolate mofetil as a key drug for treating HLH associated with SLE.